2023
DOI: 10.1021/acscatal.3c00190
|View full text |Cite
|
Sign up to set email alerts
|

Competition of CO and Acetaldehyde Adsorption and Reduction on Copper Electrodes and Its Impact on n-Propanol Formation

Abstract: Selective synthesis of n-propanol from electrocatalytic CO2/CO reduction on copper remains challenging and the impact of the local interfacial effects on the production of n-propanol is not yet fully understood. Here, we investigate the competition between CO and acetaldehyde adsorption and reduction on copper electrodes and how it affects the n-propanol formation. We show that n-propanol formation can be effectively enhanced by modulating the CO partial pressure or acetaldehyde concentration in solution. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…This approach is a useful strategy to experimentally identify potential intermediates, although it does not rule out the possibility of alternative C 2 intermediates participating in the reaction pathway. The reaction pathway for 1-propanol will not be discussed here as it has been discussed in detail elsewhere. Additionally, a small amount of hydroxyacetone (FE < 0.05%) was detected, which was also observed by Kuhl et al However, unlike 1-propanol, the reaction mechanism for hydroxyacetone formation has not yet been investigated. Interestingly, based on the reduction of hydroxycarbonyls, as shown in Figure S7, as hydroxyacetone was detected, it is also expected to form 1,2-propanediol and acetone since its reduction leads to these molecules at −1.0 V. Nonetheless, it is possible that these products were formed, but their productivity was below the chromatograph’s detection limit.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…This approach is a useful strategy to experimentally identify potential intermediates, although it does not rule out the possibility of alternative C 2 intermediates participating in the reaction pathway. The reaction pathway for 1-propanol will not be discussed here as it has been discussed in detail elsewhere. Additionally, a small amount of hydroxyacetone (FE < 0.05%) was detected, which was also observed by Kuhl et al However, unlike 1-propanol, the reaction mechanism for hydroxyacetone formation has not yet been investigated. Interestingly, based on the reduction of hydroxycarbonyls, as shown in Figure S7, as hydroxyacetone was detected, it is also expected to form 1,2-propanediol and acetone since its reduction leads to these molecules at −1.0 V. Nonetheless, it is possible that these products were formed, but their productivity was below the chromatograph’s detection limit.…”
Section: Resultsmentioning
confidence: 88%
“…For C 3 compounds, 1-propanol is the predominant product. 1-Propanol is known to be produced through the coupling of adsorbed methylcarbonyl and CO, which leads to the formation of propionaldehyde and subsequently reduced to 1-propanol. The experimental insights suggesting methylcarbonyl as a probable intermediate leading to 1-propanol were obtained by introducing a stable C 2 compound, namely, acetaldehyde, into the electrolyte and observing the resulting products after electrolysis. This approach is a useful strategy to experimentally identify potential intermediates, although it does not rule out the possibility of alternative C 2 intermediates participating in the reaction pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 This means that adjusting the adsorption strength of C 2 intermediates would affect the faradaic efficiency (FE) related to C 3 products, competing with the production of ethanol or ethylene. In this regard, previous studies have suggested that the concentration of acetaldehyde is crucial to improving n -propanol production by coupling with CO. 17…”
Section: Resultsmentioning
confidence: 99%